1999
DOI: 10.1046/j.1365-3040.1999.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of nitrate supply with growth rate, plasma membrane‐bound and cytosolic nitrate reductase, and tissue nitrate content in tobacco plants

Abstract: Activities of plasma membrane-bound nitrate reductase (PM-NR) and cytosolic nitrate reductase (cNR) in tobacco (Nicotiana tabacum L. cv. Samsun) are regulated differently, depending upon the nitrate supply to the culture medium (in sand culture). The cNR activity of roots was higher at low nitrate concentrations with the maximum at 5 mM nitrate supply and declined to low values beyond 5 mM. In contrast, the PM-NR activity of roots increased with higher nitrate concentrations with the maximum at 25 mM nitrate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…A reduction in NUE has also been observed in some C 4 species such as Miscanthus × giganteus (Danalatos et al, 2007). Furthermore, some studies have reported that excessive application of NO 3 − can reduce leaf area in Nicotiana tabacum (Stöhr, 1999), and whole plant growth in some other species such as Brassica campestris L., Brassica chinensis var. Oleifera Makino et Nenotohas and Spinacia oleracia L. (Chen et al, 2004).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A reduction in NUE has also been observed in some C 4 species such as Miscanthus × giganteus (Danalatos et al, 2007). Furthermore, some studies have reported that excessive application of NO 3 − can reduce leaf area in Nicotiana tabacum (Stöhr, 1999), and whole plant growth in some other species such as Brassica campestris L., Brassica chinensis var. Oleifera Makino et Nenotohas and Spinacia oleracia L. (Chen et al, 2004).…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, concentrations around 30 mM of N or higher have been used in plant culture, either as control (Ciompi et al, 1996) or as high N concentration (Marín et al, 2011). were replaced by CaCl 2 , CaSO 4 and K 2 SO 4 , according to Reed and Hageman (1980) and Stöhr (1999). A minimum of five plants per treatment was used and the study was repeated six times.…”
Section: Growth Chamber Experimentsmentioning
confidence: 99%
“…Stöhr (1999) (Table 2) documented the mostly superoptimum N level in hydroponics but not in sand cultures (Plhák 1994(Plhák , 1996.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of plant growth in N60 ( Figure 1B) was probably due to a detrimental effect of excess nitrate supply as observed in N. tabacum (Stöhr 1999). In this regard, CO 2 enrichment may provide a solution to mitigate the reduction of growth without decreasing N and/or protein accumulation per unit of biomass, because such a treatment was reported to promote growth without decreasing protein content per unit of fresh weight in N. tabacum (Geiger et al 1999).…”
mentioning
confidence: 83%